Perancangan Aplikasi Pengelolaan Stock Barang Pada Toko Anugrah Ilmu Berbasis Web Menggunakan Algoritma Sequential Search - Bayu Anggara; Ujang Juhardi; Marhalim Marhalim; Harry Witriyono (Jurnal Media Infotama, 2025)
Abstract—Recording inventory of goods at the Anugrah Ilmu Store still uses manual methods, namely using books, so the work takes longer and is inefficient. This research aims to design a web-based application that can help the Anugrah Ilmu store in managing stock. This research uses the waterfall method with steps, namely: (1) Analysis; (2) Design; (3) Design; (4) Code; (5) Support. The place of this research was carried out at the Anugrah Ilmu shop. This web-based application design provides a main menu, input menu and output menu. How to apply the sequential service algorithm for stock management at the web-based Anugrah Ilmu shop. You can easily search for incoming goods, outgoing goods or stock items. Can be accessed computerized Keyword: Web,Aplikasi,Waterfall